Cr effect on the durability of Pt–TM catalysts for PEMFCs. Issue 68 (23rd June 2015) - Kim, Jungdo; Lee, Eung-Seok; Chun, Yoon-Soo; Lim, Dae-Soon
Abstract : Pt–TM–Cr/C alloy catalysts were produced by a polyol method. We investigated the improvement of durability by the addition of a small amount of Cr, which is expected to prevent dissolution of transition metals. Abstract : Pt–TM–Cr/C alloy catalysts were prepared using a polyol method to improve their durability through the addition of a small amount of Cr, which is expected to prevent dissolution of transition metals (TMs). H2 PtCl6 ·H2 O, CoCl2 ·6H2 O, Ni(NO3 )2 ·6H2 O, and CrCl2 were used as precursors. X-ray diffraction was used to determine the compositions and sizes of the prepared electrocatalysts. The average sizes of the electrocatalyst particles were estimated to be 2–4 nm using the Scherrer formula. Transmission electron microscopy observations revealed that the nanoparticles were uniformly distributed on the carbon, i.e., Vulcan XC 72. The durability of the Pt–TM–Cr/C alloy catalysts was evaluated using a cell test and the durability test. According to the cell tests, Pt–TM(Co)–Cr (67 : 23 : 10)/C alloy catalysts are more durable than Pt–TM(Co)/C alloy catalysts. The stability tests showed that Cr prevents the dissolution of transition metals, which are integral to the durability of the electrode.